A three-dimensional study on methane hydrate decomposition with different methods using five-spot well - Wang, Yi; Li, Xiao-Sen; Li, Gang; Zhang, Yu; Li, Bo; Feng, Jing-Chun (Applied Energy, 2013)
The cubic hydrate simulator (CHS) is used to study the methane hydrate production behaviors in porous media with three different methods, which are the depressurization (DP) using a single well, the heat stimulation using five-spot well (HS-5S), and the heat stimulation in conjunction with depressurization using five-spot well (H&D-5S), respectively. During these experiments, the initial hydrate saturations are all 35%; environmental temperatures are all 281.15 K; and the production pressures are ranged from 4.7 MPa to 7.4 MPa. The injection temperature (T-inj) and the rate of hot water injection (R-inj) in the experiments with the HS-5S and H&D-5S methods are 10 ml/min and 160 degrees C, respectively. The analysis of hydrate decomposition shows that almost all of the hydrate can be decomposed in the hydrate reservoirs with the above methods. The H&D-55 method, which can obtain the largest volume of gas production, the highest gas production rate, and the shortest production time, is the optimal method for hydrate production in this work. (C) 2013 Elsevier Ltd. All rights reserved.